Analysis and Identification of Landuse on the East Coast of South Sumatera Using GIS - Yuanita Windusari; Laila Hanum; Margareta Sri Lestari (IAES Indonesia Section, 2015)
Analysis and identification of land use in coastal areas to study the coastal environment Sembilang National Park in South Sumatra using remote sensing system (Geoinformation System) has been conducted from June until November 2014. The objective to study the changes that occur in the coastal environment as well as to identify and estimate the area use change existing mangrove areas in Region I of the Section of Sembilang National Park Management, South Sumatra. Methods for the analysis and identification based on Landsat image data 8 in 2013 using ENVI 4.3 and Arc GIS 9.3 software as well as the conversion of ground check. The results showed the use of land in the mangrove areas in the region I of the Section of Sembilang National Park Management classified into 5 classes, namely mangrove, water area, mangrove shrubs, mainland mud, and ponds areas. The area of each class were observed in sequence as follows 8921.19 ha (41.69%) is a mangrove area; 3934.3 ha (23.28%) is water areas; 3.608,52ha (17.41%) is an area of mangrove shrubs; 1.649,11ha (9.05%) is mainland mud and settlement area; and 1.561,04ha (8.57%) is the ponds areas. The percentage of the class obtained as a result of the conversion of ground check is based on the land use map data with the total area observed.